Maintenance of PD‐1 on brain‐resident memory CD8 T cells is antigen independent - Shwetank (Immunol Cell Biol, 2017)
Infection of the central nervous system (CNS) by murine polyomavirus (MuPyV), a persistent natural mouse pathogen, establishes brain‐resident memory CD8 T cells (bT(RM)) that uniformly and chronically express programmed cell death protein 1 (PD‐1) irrespective of the expression of α(E) integrin CD103, a T(RM) cell marker. In contrast, memory antiviral CD8 T cells in the spleen are PD‐1(−), despite viral loads being similar in both the brain and spleen during persistent infection. Repetitive antigen engagement is central to sustained PD‐1 expression by T cells in chronic viral infections; however, recent evidence indicates that expression of inhibitory receptors, including PD‐1, is part of the T(RM) differentiation program. Here we asked whether PD‐1 expression by CD8 bT(RM) cells during persistent MuPyV encephalitis is antigen dependent. By transferring MuPyV‐specific CD8 bT(RM) cells into the brains of naive mice and mice infected with cognate epitope‐sufficient and ‐deficient MuPyVs, we demonstrate that antigen and inflammation are dispensable for PD‐1 maintenance. In vitro and direct ex vivo analyses indicate that CD103(−) MuPyV‐specific CD8 bT(RM) retain functional competence. We further show that the Pdcd‐1 promoter of anti‐MuPyV bT(RM) cells is epigenetically fixed in a demethylated state in the brain. In contrast, the PD‐1 promoter of splenic antiviral memory CD8 T cells undergoes remethylation after being demethylated during acute infection. These data show that PD‐1 expression is an intrinsic property of brain T(RM) cells in a persistent CNS viral infection.